2016
DOI: 10.1016/j.stemcr.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Renewal of the Holocrine Meibomian Glands by Label-Retaining, Unipotent Epithelial Progenitors

Abstract: SummaryThe meibomian and sebaceous glands secrete lipids to prevent desiccation of the ocular surface and skin, respectively. Precisely how these holocrine tissues regenerate is not well understood. To address this, we characterized keratin 5+ (K5) label-retaining cells (LRCs) and the lineage tracing of keratin 14 (K14) progenitors in mouse meibomian glands. Using the tet-off H2B-GFP/K5tTA mouse, H2B-GFP fluorescence dilutes 2-fold with every division in K5+ cell nuclei after doxycycline administration. In 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
(71 reference statements)
2
39
0
Order By: Relevance
“…To begin to understand this process we have used lineage tracing to better assess the origin and number of stem cell that participate in this process (Parfitt et al, 2016b). For these studies we have used Krt14CreER T2 -Confetti mouse, which express the conditional Brainbow 2.1 allele which incorporates open reading frames for membrane-bound mCerulean (CFP), nuclear GFPII (GFP), cytoplasmic monomeric enhanced yellow fluorescent protein (YFP) and tdimer2(12) (RFP) (Amitai-Lange et al, 2015; Di Girolamo et al, 2015).…”
Section: Meibomian Gland Stem Cellsmentioning
confidence: 99%
“…To begin to understand this process we have used lineage tracing to better assess the origin and number of stem cell that participate in this process (Parfitt et al, 2016b). For these studies we have used Krt14CreER T2 -Confetti mouse, which express the conditional Brainbow 2.1 allele which incorporates open reading frames for membrane-bound mCerulean (CFP), nuclear GFPII (GFP), cytoplasmic monomeric enhanced yellow fluorescent protein (YFP) and tdimer2(12) (RFP) (Amitai-Lange et al, 2015; Di Girolamo et al, 2015).…”
Section: Meibomian Gland Stem Cellsmentioning
confidence: 99%
“…Due to the lack of well-characterized stem cell markers for MG stem cells we used tet-off H2B-GFP/K5tTA mice (as previously shown) to verify whether K5 label-retaining cells (LRCs), which are slow-cycling progenitor cells, are localized within the HA-rich niches. 5 Although stem cell niches have still to be identified within the MG, slow-cycling progenitor cells (H2B-GFP + LRCs) have been shown to be present within the MG ductule that terminates at each acinus by using H2B-GFP/K5tTA mice after pulse/chase labeling. 5 To visualize slow-cycling epithelial progenitors, eyelids were obtained from H2B-GFP/K5tTA adult mice and the tarsal plate processed for whole mount.…”
Section: Resultsmentioning
confidence: 99%
“… 4 This lifelong differentiation and destruction of acinar cells require continual turnover of the basal layer. It has been suggested that a reservoir of progenitor cells, or slow-cycling stem cells, would have to exist within MGs to provide long-term renewal of acinar cells, 5 similar to what is seen in hair follicles, 6 , 7 and other exocrine glands, such as mammary gland, 8 lacrimal glands, 9 and salivary glands. 10 …”
mentioning
confidence: 99%
“…It was recently proposed that renewal of meibocyte could rely on a limited number of progenitor meibocytes, whereas meibomian gland duct would be derived from multiple origins. 49,50 This can explain why HMGECs induced CK expression in a pattern closely resembling that of ductal cells in response to an air-rich environment. Even if appropriate progenitor populations are found in HMGECs, they may have been exhausted because HMGECs were established from donors ranging from 35 to 85 years.…”
Section: Discussionmentioning
confidence: 99%